Bureaucratizing Sharia in Modern Indonesia: The Case of Zakat, Waqf and Family Law - Jahar, Asep Saepudin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2019)
This article examines the “bureaucratization” of Sharia in Indonesia, giving special attention to zakat, waqf and other aspects of family law. The bureaucratization of Sharia aims to modernize the legal system for Muslims in order to provide certainty and justice in solving legal disputes. While some scholars view the incorporation of Sharia into state law as an attempt at Islamization, this study argues that this process reflects increasing bureaucratization rather than Islamization. The incorporation of Sharia into state law is a project of formalizing a state-defined brand of Islam and Sharia legislation. This phenomenon has precedence in premodern Muslim governance and can be traced from the colonial period. In contemporary Indonesia, the Ministry of Religious Affairs and religious courts have played a central role in bureaucratizing Sharia. To support the argument, this study will explore Indonesian family law, including zakat and waqf.